Education Sustainability Development (ESD) Teori pada Manajemen Pendidikan Islam di Era Digital - Windy Dian Sari (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Education Sustainable Development often also referred to as Education for Sustainability is the main driver of the Sustainable Development Goals which emphasize the need for everyone to have the knowledge and skills to face the challenges of creating a more sustainable world. However, although we can find examples of Education for Sustainable Development all over the world, the potential of its implementation in Islamic Education Management effectively and its impact on achieving sustainable development goals compared to traditional curricula is often discussed.This literature review aims to encourage research and Education for Sustainable Development initiatives on Islamic Education Management in the digital era in maintaining the integrity of Islamic values. To achieve these objectives, researchers (1) describe methods and good practices for assessing the impact of Education Sustainable Development; (2) underscore the specifics of the data to be collected in the context of this assessment method; and (3) outline the conclusions of the Education for Sustainable Development impact study which has served to highlight the limitations and challenges in achieving the goals of change in Islamic education management. This study shows that Education for Sustainable Development will only achieve its goals if the pedagogical approach is updated. The studies that de facto show poor results for Sustainable Development Education allow future researchers to summarize a picture of the endogenous and exogenous factors determining sustainable behavior that must be taken into account, both in the design of impact assessment tools and in real implementation.